Comparative assessment of indoor and outdoor air environment of poultry farms in Edo State, Nigeria - Rahmatulai ADAMS; Blessing Iyore IDEMUDIA; Emmanuel Esosa IMARHIAGBE; Beckley IKHAJIAGBE; Emmanuel UKPEBOR; Frederick Osaro EKHAISE (Studia Universitatis Babeș-Bolyai. Biologia, 2022)
Intensive poultry farming creates the ideal environment for pathogen concentration and transmission. The presence of thousands of birds in an enclosed, warm, and dusty atmosphere is ideal for the transmission of infectious diseases from birds to humans. This study was conducted to assess the indoor and outdoor air quality of different poultry types in Edo State, Nigeria. The physicochemical conditions of the air around the poultry environments differed with location and poultry types. The concentrations of carbon dioxide (CO2), nitrous oxide (N2O), hydrogen sulphide (H2S) as well as particulate matter (PM10) were all within recommended limits established by the World Health Organization. However, significant elevations in Ammonia (NH3) and sulphur dioxide (SO2) levels were observed in substandard poultry farms across the locations. Total bacterial counts ranged from 1.38CFU/m5 – 90.35 x 105CFU/m3 irrespective of location and poultry type. Within the poultry types, bacteria count inside the poultry environment (3.11 x105CFU/m3) significantly differed from concentrations outside the poultry environment (22.58 x105CFU/m3, p<0.05). The Lowest microbial counts were obtained in the standard poultry farms. Molecular identifications revealed the presence of Escherichia coli, Streptococcus pyogenes, Staphylococcus aureus, Pseudomonas aeruginosa, Klebsiella pneumonia, Bacillus subtilis as the bacterial isolates whereas Fusarium oxysporum, Aspergillus niger, Rhizopus stolonifer, Trichoderma polysporum, Aspergillus fumigatus were the fungal isolates. Staphylococcusaureus was the most predominant bacterial species (25%) while Aspergillus niger was the most predominant fungal species (30%).